EVALUATION OF STOCK PORTFOLIOS’ RETURNS BUILT USING SHARPE AND SORTINO RATIOS ON BORSA ISTANBUL (Third Sector Social Economic Review, 2021)
This study aims to provide empirical insights into stocks' performance in the BIST100 index with a risk and return perspective. The risk-free rates and stocks’ closing price data of Borsa Istanbul (BIST) have been examined. The Daily data between October 3, 2016, and December 31, 2019 are used. The Sharpe and Sortino ratios are employed in the analysis. The study results have revealed that the portfolio's and stock's Sortino and Sharpe ratios are poor, suggesting that the risk-based return is low. The returns of portfolios created using the Sortino and Sharpe ratios are close to each other. Of the twenty-four portfolios built using the Sharpe ratio for twelve intervals, fourteen yielded higher returns than the BIST100 Index, and sixteen yielded higher returns than the MSCI Emerging Markets Index. Of the twenty-four portfolios built using the Sortino ratio for twelve intervals, twelve yielded higher returns than the BIST100 Index, and fifteen yielded higher returns than the MSCI Emerging Markets Index. The risk and reward ratio can be increased by diversifying the portfolio with other leveraged financial products such as options and futures contracts.
Keywords: Portfolio Investment; Sharpe Ratio; Sortino Ratio; BIST100; MSCI EM Index